2001
DOI: 10.1562/0031-8655(2001)074<0108:uliria>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light Induces Reactivation in a Murine Model of Cutaneous Herpes Simplex Virus-1 Infection¶

Abstract: We have developed a model of cutaneous herpes simplex virus-1 (HSV-1) reactivation in SKH-1 hairless mice which closely mimics the condition in humans. Sixty plaque-forming units of HSV-1 strain 17 syn+ were applied to a superficially abraded area on the lateral body wall. More than 85% of mice developed primary HSV-1 infection characterized by a zosteriform pattern of cutaneous vesiculation and ulceration. Approximately one-third of mice with primary skin lesions succumbed to neurologic disease and in the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It has been shown that UV can induce reactivation of HSV-1 virus from a mouse model (Goade et al , 2001) and this is supported by the finding of Ramos-Espinosa et al showing the high susceptibility of neurons to ultraviolet mediated DNA damage compared to reactive oxygen species mediated damage (Ramos-Espinosa et al , 2012). Neurons are highly metabolic and produce high levels of ROS which can damage DNA and deficiency in DNA damage repair pathways in neurons is associated with many neurological diseases (Fishel et al , 2007).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…It has been shown that UV can induce reactivation of HSV-1 virus from a mouse model (Goade et al , 2001) and this is supported by the finding of Ramos-Espinosa et al showing the high susceptibility of neurons to ultraviolet mediated DNA damage compared to reactive oxygen species mediated damage (Ramos-Espinosa et al , 2012). Neurons are highly metabolic and produce high levels of ROS which can damage DNA and deficiency in DNA damage repair pathways in neurons is associated with many neurological diseases (Fishel et al , 2007).…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, HSV-1 infection of differentiated neurons does not trigger the cell DDR (Lilley et al , 2005) and Fig 3. However, it has been shown that the HSV-1 genome can become reactivated by ultraviolet light (UV)-induced DNA damage in vivo (Goade et al , 2001; Ichihashi et al , 2004; Laycock et al , 1991; Loiacono et al , 2003; Shimeld et al , 1990), and in vitro (Zurlo and Yager, 1984) systems. Our results show that cellular DNA damage induced by a topoisomerase II enzyme inhibitor can enhance viral protein expression in a neuroblastoma cell line in which HSV-1 infection did not trigger the DNA damage response pathway, as measured by γ-H2Ax induction (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raised levels of galectins that include Gal-9 have been reported in some stress situations (36–39), conditions where some heat shock proteins are elevated as well in some acute infections (40) that include HSV (41, 42). So called stress situations are a well recognized prequel to HSV reactivation, which can result in disease, or be without lesions (43, 44). Whether or not the human stress scenarios include changes in levels of Gal-9 prior to HSV reactivation merits investigation.…”
Section: Discussionmentioning
confidence: 99%